Public spending in the 20th century : a global perspective - Tanzi, Vito. (Cambridge University Press, 2000)
The growth of Government since 1870. The composition of public expenditure. Revenue, deficits, and public debt. Historical evidence on government performance. The size of Government and its performance. The experience of the newly industrialized economies. Rethinking the role of the state. Fiscal rules and institutions. Blueprint for public expenditure reduction...